Histopathological spectrum of non-infectious erythematous, papulo-squamous lesions: at a teritary care institute - Agrawal, Sonal; Mishra, K. B.; Gupta, C. M. (International Journal of Research in Medical Sciences, 2018)
Background: Dermatologic disorders are common in many countries, but the spectrum varies greatly. Papulosquamous lesions of the skin are encountered with considerable frequency. There is overlap of both clinical pattern and distribution of papulosquamous skin disorders, which often makes clinical diagnosis difficult, Histopathology is highly specific and sensitive for many lesions and its remains the gold standard for most dermatological diagnosis. Methods: A prospective histopathological study of 50 cases, which was carried out in the department of dermatology and Pathology in L. N. medical college and J. K. hospital research center, over a period of 1 year. A brief history and dermatological examination was carried out, skin biopsies taken were fixed in 10% formalin and subjected for tissue processing. Followed by microscopic examination. Results: In the present study of 50 cases of papulosquamous disorders psoriasis 60% (30 Cases) was the commonest followed by lichen planus 20% (10 cases), 3% (6 cases) each of pityriasis rubra, pilaris, parapsoriasis, Pityriasis rosea, and 4% (02 cases) of seborrheic dermatitis. Commonest age-group 31-40 years was more affected, sex distribution pattern revealed a male preponderence. 30 cases showed compatible clinical as well as histopathological diagnosis. Conclusions: Key histopathological features and clinico-pathological study gives a conclusive diagnosis. The importance of specific histo-morphological diagnosis lies in the distinguishing various lesions and their prognosis.